Осесимметричные бессиловые магнитные конфигурации в плазменном потоке - Ладиков-Роев, Ю.П.; Черемных, С.О.; Яценко, В.А. (Проблемы управления и информатики, 2013)
Розглянуто математичні моделі можливих структур безсилових конфігурацій плазми. Отримано систему рівнянь в довільній ортогональній системі координат x₁, x₂, x₃, що визначає компоненти магнітного поля B₁(x₁, x₂) і B₂(x₁, x₂) через компоненту B₃(x₁, x₂) для випадку безсилової замагніченої плазмової конфігурації. Розглянуто окремі випадки рухомих конфігурацій у вигляді циліндра, еліпсоїда обертання та тора. Враховано вплив потоку плазми і руху плазми всередині конфігурації. The mathematical model of the possible structures of force-free configurations of plasma is considered. A system of equations in arbitrary orthogonal coordinate system x₁, x₂, x₃ that defines the components of magnetic field B₁(x₁, x₂) and B₂(x₁, x₂) is determined from the magnetic field component B₃(x₁, x₂) in the case of force-free magnetized plasma configuration. Special cases of moving configurations such as cylinder, ellipsoid, and torus are also considered. The effects of the plasma flux and the movement of the plasma inside the configuration are taken into account.